The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1986
DOI: 10.2105/ajph.76.3.259
|View full text |Cite
|
Sign up to set email alerts
|

The effects of infant feeding on rotavirus-induced gastroenteritis: a prospective study.

Abstract: Abstract:The relationship between feeding method and risk of rotavirus infection was studied by following a cohort of 197 infants from low income households through the winter diarrhea season of 1983-84. Fecal specimens were systematically collected and tested for the presence of rotavirus particles by electron microscopy, confirmed by ELISA. The attack rates of rotavirus gastroenteritis were similar for breast-fed and bottle-fed infants (20 per cent, 17 per cent, respectively); however, the clinical course of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
41
0
2

Year Published

1986
1986
2015
2015

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(43 citation statements)
references
References 21 publications
(1 reference statement)
0
41
0
2
Order By: Relevance
“…Studies of individuals have indicated qualitative and quantitative variation in the mucins present in human milk (62). It is thus possible that the levels of antirotaviral factors will vary depending upon genetic, nutritional, or environmental factors; these differences might explain the variable effects of breast-feeding on rotavirus infection noted in different populations (24)(25)(26)(27)(28)(29)(30). It is also possible that different strains of rotaviruses will display variable degrees of inhibition by milk glycoproteins, possibly related to varying degrees of affinity for sialic acid-containing cellular receptors (57 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies of individuals have indicated qualitative and quantitative variation in the mucins present in human milk (62). It is thus possible that the levels of antirotaviral factors will vary depending upon genetic, nutritional, or environmental factors; these differences might explain the variable effects of breast-feeding on rotavirus infection noted in different populations (24)(25)(26)(27)(28)(29)(30). It is also possible that different strains of rotaviruses will display variable degrees of inhibition by milk glycoproteins, possibly related to varying degrees of affinity for sialic acid-containing cellular receptors (57 …”
Section: Discussionmentioning
confidence: 99%
“…Breast-feeding does not provide total protection against infection and serious episodes of rotavirus infection have been noted in breast-fed infants (24)(25)(26). However, in many populations, breast-feeding lessens the severity ofdiarrhea and vomiting associated with rotavirus infection in hospitalized children (26)(27)(28). The degree of protection offered by human milk correlates only partially with the levels ofantirotavirus antibodies measured in the milk, suggesting that nonimmunoglobulin factors may play a role in the protective process (29,30).…”
Section: Introductionmentioning
confidence: 99%
“…Their results suggested that breast-feeding offered little protection against rotavirus gastroenteritis. Similarly, Duffy et al (90) found that, although rotavirus attack rates were similar between breast-and bottle-fed infants, rotavirus infection in breastfed infants was milder and of shorter duration than in bottle-fed babies.…”
Section: Epidemiologymentioning
confidence: 91%
“…The MMU vaccine might also be effective in early infancy, when passively acquired antibodies are at a high level and when less side reactions may occur. In such a population, a more attenuated vaccine may not take, as was shown to be a problem with the RIT 4237 vaccine (380 (90,206). Thus, the primary purpose of therapy is to correct these problems by providing adequate hydration to maintain blood volume, electrolyte homeostasis, and acid-base balance (90).…”
Section: Vol 2 1989mentioning
confidence: 99%
“…Virtually all children are infected at least once within the first 5 years of life, with the peak incidence widely quoted as occurring between 6 and 24 months of age (5,7,11,13,14,16,(20)(21)(22)(23). For the first few months of life, infants are thought to be partially protected by maternal antibodies acquired transplacentally or through breast feeding (24)(25)(26). The Advisory Committee on Immunization Practices currently recommends the initiation of the rotavirus vaccine series at 2 months of age, although the first dose can be given as early as age 6 weeks (27,28).…”
Section: Introductionmentioning
confidence: 99%